Improving Mood and Cognitive Symptoms in Huntington's Disease With Cariprazine Treatment - Molnar, Maria Judit; Molnar, Viktor; Fedor, Mariann; Csehi, Reka; Acsai, Karoly; Borsos, Beata; Grosz, Zoltan (Frontiers in Psychiatry, 2022)
In Huntington’s disease (HD), the main clinical symptoms include depression, apathy, cognitive deficits, motor deficiencies and involuntary movements. Cognitive, mood and behavioural changes may precede motor symptoms by up to 15 years. The treatment of these diverse symptoms is challenging. Tetrabenazine and deutetrabenazine are the only medications specifically approved for Huntington's chorea, but they do not affect the non-motor symptoms. For these, antidepressants, antipsychotics, and benzodiazepines have demonstrated benefit in some cases and can be used off-label. These drugs, due to sedative side effects, may negatively influence cognition. Sixteen patients having HD received a 12-week off-label cariprazine (CAR) treatment (1.5 -3 mg/day). Cognitive performance and behavioural changes were measured by the Addenbrooke Cognitive Examination (ACE) test, the Cognitive and Behavioural part of the Unified Huntington’s Disease Rating Scale (UHDRS), and the Beck Depression Inventory (BDI). Mixed model for repeated measures was fitted to the data, with terms of visit, baseline (BL) and their interaction. Cariprazine (CAR) treatment resulted in the following changes from BL to week 12, respectively: the mean score of BDI decreased from 17.7 + 10.7 to 10.0 + 10.7 (p<0.0097), while the Behavioral Assessment score of the UHDRS decreased from 54.9 + 11.3 to 32.5 + 15.4 (p<0.0001); ACE score increased from 75.1 + 11.0 to 89.0 + 9.3 (p<0.0001); Cognitive Verbal Fluency score from 6.2 + 2.5 to 7.7 + 2.7 (p<0.0103); Symbol Digit Test from 9.2 + 6.9 to 12.3 + 8.9 (p<0.0009). Mild akathisia was the most frequent side effect, presenting in 2 out of 16 patients (12.5%). We conclude that CAR had a positive effect on depressive mood, apathy and cognitive functions in patients with early stage of HD. Based on the neurobiological basis of these symptoms, CAR can improve the dopamine imbalance of the prefrontal cortex. This draws attention to the transdiagnostic approach which supports the further understanding of the similar symptomatology of different neuropsychiatric disorders and helps to identify new indications of pharmaceutical compounds.